Health-related quality of life and its influencing factors in rural chronic disease patients in Ningxia Hui Autonomous Region - Li MA; Gang-jun LIU; Hui QIAO (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine health-related quality of life (HRQOL) and its influencing factors among chronic disease patients in rural areas of Ningxia Hui Autonomous Region (Ningxia) and to provide references for the prevention, control, and management of chronic diseases in the population. MethodsTotally 3 267 rural households were recruited in 2 counties of Ningxia with stratified random cluster sampling and a questionnaire survey was conducted among family members of the selected households in February 2019. Then from all the family members, we identified 2 700 chronic disease patients aged ≥15 years and the HRQOL of the patients were evaluated using Euro - Quality of Life - 5 Dimension (EQ-5D). Results Of the 2 700 patients, 42.4% (1 146) reported pain/discomfort; 25.1% (677) reported anxiety/depression; and 24.6% (664), 22.9% (618), and 13.7% (369) reported problems in mobility, usual activities, and self-care, respectively. The health utility value for all the patients was 0.93 ± 0.12. The results of Tobit regression model analysis demonstrated that the patients with following characteristics were more likely to have a lower health utility value: being female, at ages of 51 - 60/61 - 70/ > 70 years compared to those aged ≤ 50 years, and without formal education in comparison with those with formal education. Conclusion The health-related quality of life is poor and the health utility value is mainly influenced by gender, age and education among chronic disease patients in rural regions of Ningxia.